PENINGKATAN HASIL BELAJAR SISWA KELAS V PADA MATERI CAHAYA DAN SIFATNYA MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DI UPTD SD INPRES OEBA 2 KOTA KUPANG - Inosensia Klau; Hartoyo Yudhawardana; Netty E. A Nawa (STKIP Subang, 2025)
This study aims to improve the learning outcomens of fifth-grade students on the topic of “Light and its Properties’’ through the implementation of the Problem Based Learning (PBL) model at UPTD SD Inpres Oeba 2 Kota Kupang. The research is a Classroom action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects iof the study were 25 fifth-grade students. Data collection techniques included observation and tests. The results showed an improvement in students’ learn9ng outcomes from Cycle I to Cycle II. In Cycle I, only 10 students (40%) achived the minimum mastery criteria. In cycle II, thenumber of students who achieved mastery increased to 23 (92%). It can be concluded that the impementtation of the PBL model is effective in improving students’ learning outcomes.